Simultaneous removal of tetracycline and manganese (II) ions from groundwater using manganese oxide filters: Efficiency and mechanisms. (August 2021) - Cheng, Ya; Zhang, Yongzhi; Xiong, Weiyao; Huang, Tinglin
Abstract: Co-contamination of antibiotics and manganese (Mn 2+ ) prevailing in groundwater enhances the difficulties for water treatment. In this study, a manganese oxide (MnOx) filter media, which was developed for the removal of Mn 2+ and ammonium by catalytic oxidation, was adopted to simultaneously remove Tetracycline (TET) and Mn 2+ from groundwater. The experimental results show that TET removal is the result of the synthesis of adsorption and oxidation, and the presence of a certain concentration of Mn 2+ (1 and 5 mg/L) in the influent significantly reduces the TET removal capacity of the filter media. Similarly, the presence of TET decreases the Mn 2+ removal capacity. The breakthrough curves could be fully described with the Thomas model. The surface characteristics and structures of the MnOx filter samples were determined using scanning electron microscopy, X-ray diffraction, and X-ray photoelectron spectroscopy. Various analysis results reveal that the high-valence manganese in the crystal lattice of MnOx is consumed during TET removal, which leads to lattice enlargement. However, during the simultaneous removal of Mn 2+ and TET, TET consumes high-valence manganese produced by autocatalysis, especially trivalent manganese. The mechanism underlying the simultaneous removal of Mn 2+ and TET by the MnOx filter media is revealed in this study. Therefore, this work provides guidance for the prevention and control of antibiotic contaminants during groundwater treatment. Graphical abstract: Unlabelled Image Highlights: Manganese oxide (MnOx) filter media can remove Mn 2+ and TET simultaneously. TET removal efficiencies were negative correlated with influent manganese concentration. Absorption and oxidation were involved in TET removal process. Possible structural evolution characteristics of the manganese oxide were proposed.